HPV Infection in Cervical and Other Cancers in Saudi Arabia: Implication for Prevention and Vaccination - Alsbeih, Ghazi (Frontiers in Oncology, 2014)
HPV is closely associated with cervical cancer that the incidence of this tumor is regarded as a surrogate marker for HPV infection in countries lacking epidemiological studies. HPV is also implicated in subsets of anogenital and oro-pharyngeal cancers. Although cervical cancer is the third most common cancer in women worldwide, its reported incidence is low in Saudi Arabia, ranking number 12 between all cancers in females and accounts only for 2.4% of all new cases, despite the lack of national screening programs. However, the limited available studies from Saudi Arabia indicate that HPV prevalence and genotypes’ distribution in invasive cervical cancer show similar pattern as in the world. Cytology screening (Pap Smear) and HPV vaccinations are the two preventive measures against cervical cancer. The two available vaccines are effective against the two most common HPV genotypes (HPV-16 and 18). Since 92% of cervical tumors in the Kingdom are infected with HPV of which 78% are HPV-16 and 18 genotypes, vaccination is expected to protect against more than two-third of cervical cancers in Saudi Arabia. Nevertheless, due to its low incidence (2.1/100,000 women), a proper cost-effectiveness analysis is required to justify the implementation of a costly vaccine bearing in mind that HPV could potentially be associated with about 3% of all cancers. However, further studies are needed to ascertain the real prevalence of HPV at the population level at large, its association with various types of cancers and also the impact of local tradition and emerging behavioral trends that could affect HPV transmission and consequently the effectiveness of applying national vaccination program.